KETIKA AYAT MENJADI KONTEN: OTORITAS ALKITAB DAN FENOMENA MIKRO-TEOLOGI DI MEDIA SOSIAL (MEDSOS) - Berty Kristina Napitupulu; Agus Marulitua Marpaung (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2026)
The digital era is marked by changes in how Christians view, use, access, understand, and even interpret the Bible, particularly through social media platforms like TikTok, Instagram (IG), and Facebook (FB), which allow anyone to consume spiritual content instantly in visual form. Bible verses are packaged into short content that aligns with existing algorithm logic, regardless of their original historical and literary context. This is a form of fragmented or pragmatic micro-theology. The purpose of this research is to analyze how Bible verses are interpreted on social media, evaluate how well these interpretations align with classical hermeneutical principles, and explain how these patterns influence people's views on the authority of the Bible in the digital world. The qualitative-descriptive method was used to analyze through content observation, hermeneutic literature study, and comparison between digital and classical exegesis. The findings of this study indicate that algorithms play a major role in determining authority, that virality and content aesthetics have more influence on theological legitimacy than hermeneutical depth. The study concludes that the algorithms have shifted authority from canonical texts and faith communities to digital metrics, implying that the church must develop a digital hermeneutic approach that connects the complexity of classical theology with the dynamics of current social media.